Molecular interactions between some amino acids and a pharmaceutically active ionic liquid domiphen DL-mandelic acid in aqueous medium at temperatures from 293.15 K to 313.15 K. (November 2019) - Yan, Zhenning; Chen, Xue; Liu, Liyun; Cao, Xingxing
Highlights: Densities, conductivities, fluorescence and UV–vis absorption spectroscopy of amino acid + [DOM][MAN] + water mixtures. Hydrophilic-hydrophobic and hydrophobic-hydrophobic interactions between [DOM][MAN] and amino acids are dominate. Rise in temperature increases the cmc values of [DOM][MAN] and the V 2, φ 0 values of amino acids. Addition of amino acids in water decreases the values of cmc and N agg of [DOM][MAN]. The size of alkyl chain of amino acids affects the interaction between [DOM][MAN] and amino acids. Abstract: Molecular interactions between some amino acids (glycine, l -alanine, l -valine andl -leucine) and a pharmaceutically active ionic liquid domiphen DL-mandelic acid ([DOM][MAN]) in aqueous solution at various temperatures have been studied by means of volumetric, conductivity and spectroscopy measurements. Density data were used to derive standard partial molar volume, V 2, φ 0 standard partial molar expansibility, E φ 0, standard transfer volume, Δt V 0, isobaric thermal expansion coefficient, α0 and hydration number, n H of amino acids. On the basis of the experimental conductivity and fluorescence spectroscopy data, the aggregation behaviour of [DOM][MAN] in aqueous amino acid solutions was investigated. Critical micelle concentration, cmc, aggregation number, N agg, some thermodynamic functions, Δ G m 0, Δ H m 0, Δ S m 0 and Δ C p 0 of micellization for [DOM][MAN] have been obtained. Effect of concentration and temperature on the obtained parameters has been discussed. Binding constant K b for amino acid-[DOM][MAN] complex estimated using the UV–vis spectroscopic data approved that the solute-solvent interactions were strengthened by elevating the size of alkyl part of amino acids.